The effectiveness and safety of the rapid titration strategy of background controlled-release oxycodone hydrochloride for patients with moderate-to-severe cancer pain: A retrospective cohort study - Feng, Weineng; Wang, Yufeng; Ran, Fengming; Mao, Yong; Zhang, Helong; Wang, Qifeng; Lin, Wen; Wang, Zhidong; Hu, Jianli; Liao, Wangjun; Zhang, Tao; Chu, Qian; et al. (Frontiers in Medicine, 2022)
Background: Oxycodone hydrochloride is a semisynthetic narcotic analgesic agent. This study aimed to explore optimal titration strategy of controlled-release (CR) oxycodone hydrochloride in patients with cancer pain. Methods: 258 patients, who used regular strong opioids (morphine and CR oxycodone hydrochloride) for cancer pain across 25 three grade class hospitals in China during January 15th 2017 to April 30th 2017, were retrospectively studied. The patients were divided into 4 groups according to treatment regimens titrated. The pain remission rate and numeric rating scale (NRS) of cancer pain was recorded at 0, 12, 24, 36, 48, 60, 72 h after opioid titration. The incidence of adverse events (AEs) with therapy were also observed. Results: 12 h after treatment, pain remission rate of Group B, C and D was significantly higher (P<0.001) than Group A. For the complete remission rate, there were also significant differences among the four groups (P<0.001). No significant difference was found among four groups for pain remission rate at 24, 72 h after treatment. Multiple comparison of NRS scores showed that the both Group B and C varied significantly with Group D (P=0.028, P=0.05, respectively), showing superior analgesic effect over Group D. AEs were significantly different among groups (P<0.01), with the most frequent AEs in Group A, lowest in Group B. Conclusion: The rapid titration strategy of background CR oxycodone hydrochloride was effectiveness and safety in patients with moderate-to-severe cancer pain.